PROSPECTS OF USING THE CAVITATION PHENOMENON IN OIL REFINING (ChemChemTech, 2023)
Over the past decades, the balance of hydrocarbon production shows a rising trend of production heavy, high-viscosity oil. Their transportation and refining involves higher energy costs, which can be reduced by using the innovative oil treatment method based on the creation of the cavitation phenomenon. It should be noted that the information about the change in oil characteristics as a result of cavitation treatment is contradictory. This also applies to the nature of the change in the properties and the stability of these changes over time. In some cases, the different nature of the changes is associated with the group composition of the samples. This paper is devoted to the study of the influence of cavitation oil treatment of different nature on their fractional composition and characteristics of individual fractions. Here was an attempt to determine the optimal time of fractionation of oil (after processing) in order to obtain the greatest output of light fractions. Heavy and light oil from the Ilsk field (Krasnodar Krai) were selected as the research subjects. The study of the influence of the treatment conditions on the viscosity of oil products was carried out on the sample of straight-run fuel oil (SRFO) provided by AO «Gazpromneft - MNPZ», obtained at the ELOU-AVT-6 unit. Cavitation processing of samples was carried out in the apparatus of HPH «Donor-2». The density of the samples and their fractions were determined according to GOST 3900-85 «Oil and petroleum products. Methods for the determination of the density». Fractional composition of petroleum in accordance with GOST 2177-99 «Petroleum products. Methods of determination of fractional composition». Vacuum distillation was used to determine the fractional composition of dark petroleum products. Kinematic viscosity was determined by GOST 33-2016. The conducted researches have shown the prospect of using the cavitation phenomenon in oil refining processes. It is possible to change (reduce) the viscosity of the oil product, to increase the yield of fractions with lower boiling points by using this phenomenon. The efficiency of the treatment increases with the increase in the density of the oil product. The results do not confirm information about the post-effect of cavitation treatment of petroleum products, when changes in the characteristics of the sample continue for some time after refining. By measuring the viscosity of the fuel oil sample, it is shown that the relaxation of the characteristics begins after treatment and it is most noticeable during the first 5 days after treatment. This allows us to recommend to treatment the sample immediately prior to fractionation. It should also be noted that as a result of cavitation treatment, not only dark but also light petroleum fractions are affected, and in all of these fractions along destruction and isomerization reactions, there are also processes of compaction.